PEMANFAATAN VIDEO INTERAKTIF TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SELAMA PANDEMI COVID-19 PADA PEMBELAJARAN PAI DAN BUDI PEKERTI KELAS X SMA NEGERI 2 MALANG - Maria Ulfa; Abd Jalil; Arief Ardiansyah (VICRATINA, 2022)
The acceleration in educational technology encourages teachers to use media inlearning that is considered appropriate. There are many choices of learning ideas thatcan be applied with the help of technology, one of the uses of technology results ineducation is the use of interactive videos in the learning process. The use of media isable to provide an increase in student motivation in learning. In this thesis research,the author uses a qualitative approach because this study aims to describe the resultsof data processing in the form of words and general descriptions that occur in the field.Based on the results of the research that has been carried out, the researchers concludethat the use of interactive videos in motivation and learning outcomes during thecovid19 pandemic in the PAI and Budi Pekerti learning process for class X SMA Negeri2 Malang. The characteristics of the right video on students' motivation and learningoutcomes are interactive video learning media that are easy for students and alsoteachers. In this regard, the results of using interactive videos can increase studentmotivation and learning outcomes